2019
DOI: 10.1098/rstb.2018.0294
|View full text |Cite
|
Sign up to set email alerts
|

The rabbit papillomavirus model: a valuable tool to study viral–host interactions

Abstract: One contribution of 16 to a theme issue 'Silent cancer agents: multi-disciplinary modelling of human DNA oncoviruses'.Cottontail rabbit papillomavirus (CRPV) was the first DNA virus shown to be tumorigenic. The virus has since been renamed and is officially known as Sylvilagus floridanus papillomavirus 1 (SfPV1). Since its inception as a surrogate preclinical model for high-risk human papillomavirus (HPV) infections, the SfPV1/rabbit model has been widely used to study viralhost interactions and has played a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 102 publications
1
25
0
Order By: Relevance
“…Therefore, a human papillomavirus cannot infect any animal [50]. Our laboratory has expertise in both the CRPV/rabbit and the MmuPV1/mouse models [15,16]. Armed with these preclinical models, we demonstrated that ( 1) Viral sequences could be detected in the blood of infected animals; (2) Virus introduced into the blood yielded tumours at both cutaneous and mucosal sites; (3) CRPV DNA introduced into the blood yielded papillomas at prepared skin sites; (4) Similar mechanisms are used for infections via the blood and by direct application of virus to the skin as determined by RNA-seq analysis; (5) Transfusion of blood from an animal that had received virus via intravenous infection to a naïve sibling resulted in papillomas in the transfusion recipient; (6) Virus introduced via intravenous delivery yielded infections at the stomach as well as the normally permissive sites, and (7) Blood from animals with active infections could induce infections in naïve mice when transfused into these animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a human papillomavirus cannot infect any animal [50]. Our laboratory has expertise in both the CRPV/rabbit and the MmuPV1/mouse models [15,16]. Armed with these preclinical models, we demonstrated that ( 1) Viral sequences could be detected in the blood of infected animals; (2) Virus introduced into the blood yielded tumours at both cutaneous and mucosal sites; (3) CRPV DNA introduced into the blood yielded papillomas at prepared skin sites; (4) Similar mechanisms are used for infections via the blood and by direct application of virus to the skin as determined by RNA-seq analysis; (5) Transfusion of blood from an animal that had received virus via intravenous infection to a naïve sibling resulted in papillomas in the transfusion recipient; (6) Virus introduced via intravenous delivery yielded infections at the stomach as well as the normally permissive sites, and (7) Blood from animals with active infections could induce infections in naïve mice when transfused into these animals.…”
Section: Discussionmentioning
confidence: 99%
“…For IHC, an in-house anti-MmuPV1 L1 monoclonal antibody (MPV.B9) and a rabbit polyclonal antibody against MmuPV1 E4 protein (a generous gift from Dr John Doorbar) were used on FFPE sections. For ISH, a biotin labelled 2794 bp EcoRV/SacII sub-genome fragment of CRPV and 3913 bp EcoRV/BamHI sub-genomic fragment of MmuPV1 were used as in situ hybridization probes for the detection of CRPV and MmuPV1 DNA in tissues respectively [15,37]. Counterstaining for ISH was Nuclear Fast Red (American MasterTech, Inc.) and for IHC was hematoxylin (Thomas Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbits have long served as the gold standard model for the study of PV pathogenesis, as well as its associated diseases and cancers ( Cladel et al, 2019 ). Domestic rabbits are susceptible to infection by the cutaneous-tropic cottontail rabbit PV (CRPV) and the mucosal-tropic rabbit oral PV (ROPV) ( Christensen et al, 2000a , b , c ; Peh et al, 2002 ; Wilgenburg et al, 2005 ; Maglennon et al, 2011 ).…”
Section: Gene Edited Rabbits For Translational Studies Of Human Papilmentioning
confidence: 99%
“…Domestic rabbits are susceptible to infection by the cutaneous-tropic cottontail rabbit PV (CRPV) and the mucosal-tropic rabbit oral PV (ROPV) ( Christensen et al, 2000a , b , c ; Peh et al, 2002 ; Wilgenburg et al, 2005 ; Maglennon et al, 2011 ). These preclinical models have proven valuable for understanding the pathogenesis of high-risk papillomavirus infection and cancer development ( Breitburd et al, 1997 ; Brandsma, 2005 ; Christensen et al, 2017 ), as well as played a pivotal role in the development of the two currently available prophylactic vaccines ( Breitburd et al, 1995 ; Christensen et al, 1996 ; Cladel et al, 2019 ). In addition, the rabbit model has been used widely to test anti-viral and anti-tumor therapies ( Christensen et al, 2000c , 2001 , 2014 ).…”
Section: Gene Edited Rabbits For Translational Studies Of Human Papilmentioning
confidence: 99%